To solve the equation \( 5(2x - 5) - 4x - 4 = -11 \), let's break it down step by step.
-
Distribute the \( 5 \) into the parentheses: \[ 5 \cdot 2x - 5 \cdot 5 = 10x - 25 \] So the equation becomes: \[ 10x - 25 - 4x - 4 = -11 \]
-
Combine like terms on the left side: \[ (10x - 4x) + (-25 - 4) = 6x - 29 \] Therefore, we have: \[ 6x - 29 = -11 \]
-
Next, add \( 29 \) to both sides of the equation: \[ 6x - 29 + 29 = -11 + 29 \] This simplifies to: \[ 6x = 18 \]
-
Finally, divide both sides by \( 6 \): \[ x = \frac{18}{6} = 3 \]
The solution to the equation is: \[ \boxed{3} \]